Reformasi Birokrasi: Penerapan Teknologi Informasi Dalam Meningkatkan Pelayanan Publik - Wiwik Anggraeni; Imelda Dian Rahmawati (Politeknik Kampar, 2024)
Bureaucratic reform is an urgent need to improve the quality of the state civil apparatus and realize good governance in Indonesia. Bureaucracy is often considered complicated, slow and unprofessional. To address this, the government is committed to various reform initiatives, including the application of information technology in public services. This research aims to explore the contribution of information technology in improving public services as part of bureaucratic reform. By adopting information and communication technology (ICT) in e-government systems, it is hoped that administrative processes can be accelerated, efficiency increases, and the reach of public services expands. However, ICT implementation faces challenges such as limited human resources, cyber threats, privacy issues, inadequate infrastructure, and resistance to change. This research will analyze the factors that influence the successful implementation of information technology in public services and identify strategies to overcome these obstacles. It is hoped that the research results will provide policy recommendations that support bureaucratic reform, so that public services become more efficient, transparent and responsive to community needs.